Bendix MA-026 Mass Sequencer - Bendix Corporation (1970)
Series of photographs depicting the interior and exterior of a Bendix Corporation MA-026 Mass Sequencer designed for use with the Bendix Time-of-Flight Mass Spectrometer. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Mass spectrometers